The combined evaluation of preoperative serum CEA and postoperative tissue CEA as a prognostic factor in stages 0–IV colorectal cancer: a retrospective cohort study - Guojun Tong; Guojun Tong; Hui Li; Yan Shen; Zhenhua Tan; Hai Qian (Frontiers in Medicine)
BackgroundThe roles of preoperative serum carcinoembryonic antigen (sCEA) and postoperative tissue carcinoembryonic antigen (tCEA) have been extensively studied in isolation in colorectal cancer (CRC). However, the combined role of sCEA and tCEA remains inadequately described.MethodsA total of 1,757 retrospective cases of stage 0–IV CRC from January 2006 to January 2016 in our institution were included. Clinicopathological features and follow-up data were collected. Stage 0 was combined with stage I. sCEA levels were classified as normal or high (>10 ng/mL), while tCEA levels were categorised into three grades (+, ++, and +++). This resulted in six combined groups (2 × 3). ANOVA and cross-tabulation were employed to analyse continuous and categorical data, respectively. Univariate and multivariate analyses were conducted using Cox regression. All data were analysed using SPSS 27 and R 4.3.1.ResultsSome clinicopathologic features differed significantly among the combined CEA test groups (all p < 0.05). The receiver operating characteristic (ROC) curves for sCEA, tCEA, and combined CEA exhibited significant differences in five-year OS with death as the input variable (all p < 0.05). The area under the curve (AUC) for combined CEA was the highest, indicating the value of this study. Cox regression analysis demonstrated that tumour location, T stage, differentiation, chemotherapy, TNM stage, tCEA, and combined CEA were significant in the univariate analysis; however, tCEA was not significant (p = 0.096) in the multivariate analysis among these seven variables. Five-year OS analysis revealed that sCEA, tCEA, and combined CEA were not significant in stages 0 & I–II (all p > 0.05) but were significant in stages III–IV (all p < 0.05), except for tCEA in stage IV (p = 0.24) as per K–M and univariate analysis. No significant difference was observed between sCEA and tCEA (p = 0.55, 0.095), whereas combined CEA demonstrated a significant difference (p < 0.001) in both univariate and multivariate analyses.ConclusionsCEA, tCEA, and combined CEA exhibit prognostic roles in stages III–IV of CRC, with only combined CEA serving as an independent factor in these stages.